Дозвільна політика держави: питання формування та реалізації - Джафарова, О. В.; Dzhafarova, O. V.; Джафарова Олена В'ячеславівна (Вісник Запорізького національного університету. Юридичні науки. – 2015. – № 4 (1). – С. 95–102, 2015)
У статті під регуляторною (дозвільною) політикою держави запропоновано розуміти окремий напрям діяльності держави, спрямований на вироблення оптимальної моделі поєднання існуючого правового інструментарію, за допомогою якого забезпечується виконання цілей, що стоять перед державою в економічній, інформаційній, екологічній та інших сферах. Виокремлено такі основні складники регуляторної політики в Україні: а) публічне обговорення проектів нормативно-правових актів органів публічної адміністрації; б) регуляторну політику, що має бути гнучкою та працювати на випередження потреб суспільства; в) перегляд чинних регуляторних актів із метою впорядкування нормативного середовища; г) запровадження нових регуляторних заходів.

In the article, the regulatory (authorization) policy of the state understood proposed separate line state activity, aimed at developing an optimal model of combining the existing legal instruments by which the objectives provided facing the state in the economic, informational, ecological and other spheres. Thesis there is determined the main components of regulatory policy in Ukraine: a) public discussion of draft legal acts of public administration; b) Regulatory policies should be flexible and work to advance the needs of society; с) reviewing existing regulations in order to streamline the regulatory environment; d) the introduction of new regulatory measures. Background is that the aim of public policy is to ensure national security components (economic, environmental, informational, internal), innovative development of the country and allowing activity is just one of the legal tools to ensure implementation of the above. The Law of Ukraine “On the central executive power” is in ministries duty on public policy. That is, it forms the Cabinet of Ministers of Ukraine public policy in general and in the particular field in particular. The conclusions are that under the regulatory (authorization) policy of the state should be understood separate direction of state activity, aimed at developing an optimal model of combining the existing legal instruments by which secured the objectives facing the country in economic, informational, environmental and other areas. The main components of regulatory policy in Ukraine should be: a public discussion of draft legal acts of the public administration before their final adoption, obligatory consideration all public comments and suggestions, and the need to publicly argue that the regulation does not pursue their narrow interests designed to limits and takes into account all business relations. Emphasis should be placed on those subjects that directly affect the introduction of the regulatory act; Regulatory policies should be flexible and work to advance the needs of society; review existing regulations to streamline the regulatory environment, verify real consequences of adjustments, selection of the adjustments that need to change other more cost-effective means, and who did cancel as those that are either not be replaced or fulfilled their regulatory function, as the object of their regulation made new signs; the introduction of new regulatory measures must focus on the tasks of national security, to be economically and financially sound and have a simple and transparent procedure implementation.

В статье под регуляторной (разрешительной) политикой государства предложено понимать отдельное направление деятельности государства, направленное на выработку оптимальной модели объединения существующего правового инструментария, с помощью которого обеспечивается выполнение целей, которые стоят перед государством в экономической, информационной, экологической и других сферах. Выделены такие основные составляющие регуляторной политики в Украине: а) публичное обсуждение проектов нормативно-правовых актов органов публичной администрации; б) регуляторная политика, которая должна быть гибкой и работать на опережение потребностей общества; в) пересмотр действующих регуляторных актов с целью упорядочения нормативной среды; г) введение новых регуляторных мер.
Разрешительная политика государства: вопрос формирования и реализации
Permit state policy: formation and realization aspect
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; дозвільна політика; дозвільна діяльність; органи публічної адміністрації; регуляторна політика; зарубіжний досвід; licensing policy; licensing activities; public administration bodies; elements of regulatory policy; foreign experience; разрешительная политика; разрешительная деятельность; органы публичной администрации; регуляторная политика; зарубежный опыт